Mucosal Healing Effectiveness and Safety of Anaprazole, a Novel PPI, vs. Rabeprazole in Patients With Duodenal Ulcers: A Randomized Double-Blinded Multicenter Phase II Clinical Trial - Shu, Xu; Zhu, Zhenhua; Fu, Yu; Zhang, Zhenyu; Wang, Jiangbin; Li, Xing; He, Shuixiang; Fan, Huizhen; Liu, Side; Zhang, Guoxin; Tang, Jianhua; Huang, Caibin; et al. (Frontiers in Medicine, 2021)
Background: Proton pump inhibitors (PPIs) have been widely used to treat patients with active duodenal ulcers. Although existing PPIs have shown great efficacy, many scientists are still devoted to developing more effective PPIs with better safety profile. Herein, we aimed to compare the safety and efficacy of anaprazole, a novel PPI, to that of rabeprazole. Methods: In this multicenter, randomized, positive-controlled, double-blinded, parallel-group phase II clinical trial, a total of 150 qualified patients with endoscopically confirmed active duodenal ulcers were randomized (1:1:1) to receive rabeprazole 10 mg, anaprazole 20 mg or anaprazole 40 mg for 4 weeks. The ulcer healing rates after 4 weeks of treatment were compared between groups by independent central review and investigator review. In addition, symptoms and safety were evaluated. Results: Based on the independent central review, the ulcer healing rates of the 10 mg rabeprazole, 20 mg anaprazole and 40 mg anaprazole groups were 88.0%, 85.1% and 87.5%, respectively, in the FAS population and 88.9%, 86.0% and 90.9%, respectively, in the PPS population. The ulcer healing rate difference between anaprazole 20 mg and Rabeprazole 10 mg is -2.9% (95% CI, -16.5%~10.7%), and -0.5% (95% CI, -13.5%~12.5%) between anaprazole 40 mg and Rabeprazole 10 mg, in the FAS population. Based on the investigator review, the ulcer healing rates of the 10 mg rabeprazole, 20 mg anaprazole and 40 mg anaprazole groups were 72.0%, 70.2% and 77.1%, respectively, in the FAS population and 75.6%, 72.1% and 79.5%, respectively, in the PPS population. The ulcer healing rate difference between anaprazole 20 mg and Rabeprazole 10 mg is -1.8% (95% CI, -19.8%~16.3%), and 5.1% (95% CI, -12.2%~22.3%) between anaprazole 40 mg and Rabeprazole 10 mg, in the FAS population. Most patients (>90%) eventually achieved complete symptom relief. The incidence rates of adverse events were of no significant differences among the treatment groups. Potential better liver tolerance was observed in two anaprazole dose groups than rabeprazole 10 mg group. Conclusion: Both at a dosage of 20 mg and 40 mg daily, anaprazole, is effective with good safety profile in the treatment of active duodenal ulcers in this Phase 2 study.